Regression and Correlation Analysis in Assessing Factors Influencing Customer Satisfaction in the Healthcare Sector - Surjono, Welly (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study uses regression and correlation analysis to evaluate the factors influencing customer satisfaction in the healthcare sector. The primary focus is on three key variables: service quality, medical staff competence, and facility availability. Service quality encompasses various dimensions, including reliability, responsiveness, assurance, empathy, and tangible aspects, collectively shaping patients' perceptions of the services received. The results reveal that service quality exerts the most significant influence on customer satisfaction, as evidenced by a high regression coefficient, underscoring the importance of these dimensions in enhancing satisfaction levels. Medical staff competence is also critical to customer satisfaction, although its impact is less pronounced than service quality. Competence includes medical knowledge, clinical skills, and effective communication with patients. Meanwhile, facility availability demonstrates a weaker correlation with customer satisfaction, though it remains a relevant aspect of healthcare services. These findings offer strategic insights for hospital and clinic management in designing and implementing policies to improve customer satisfaction. By prioritizing enhancements in service quality and medical staff competence, along with maintaining adequate facilities, healthcare institutions can achieve higher customer satisfaction levels and sustain service quality over time.